"Ser professora de inglês" na pandemia da covid19: diálogos, valorações e identidades em um estudo de caso - Oliveira, Ana Clésia de (2023)
The pandemic caused by the Covid-19 virus surprised the world and caused social changes at a speed rarely seen in history. The changes caused by the virus have confronted the routine of society as a whole to an extent never before imagined. In the educational context, teaching institutions and teachers around the world were forced to "adapt" in a minimum of time. Thus, adopting a view of language that encompasses its inextricable cultural, social and ideological contexts, this research aims to investigate how the teaching identity of an English language teacher has been affected (HALL, 2006, 2000; SILVA 2001; WOODWARD 2000; BAUMAN, 2005), tracing her valuations about her teaching practice throughout the period of emergency remote teaching during the pandemic. Based on the studies of Bakhtin and his Circle (BAKHTIN, 1979; 2006; 2003; 1996; BRAIT 2004; FARACO 2021; SOBRAL 2021; GERALDI, 1996). The research of qualitative approach (DENZIN; LINCOLN, 2006) is a case study (LUDKE; ANDRÉ 1986) and was conducted with an elementary school teacher. The empirical material was generated in the second half of 2021. To reach the objective of this study the following research tools were administered: initial questionnaire, three reflective sessions, and final semi structured interview recorded in video and audio via google meet. The data point out that the teacher had her teaching identity affected by several factors: the context itself and its physical and psychological implications, the lack of her interlocutor (student/s) in the classroom, the discourses addressed to the teaching profession during the emergency remote teaching, among others. Regarding the valuations in relation to teaching/learning, a weariness influenced by different conditions was noticed. The reflective sessions provided changes in conceptions, thus making it possible to understand the meanings that could produce significant changes in the pedagogical work. They also promoted transformations in the way the participant understands herself and her teaching.